The impact of a pharmacy student‐led community naloxone education program in high school, college, and pharmacy students on knowledge, preparedness, and responsiveness in the event of an opioid overdose. Issue 3 (17th January 2022) - Azad, Atra; Levy, Jason; Kefer, Emily; Loubani, Lamees; Brinton, Meghan; Wollen, Joshua
Abstract: Introduction: In response to the opioid overdose epidemic, initiatives have been established to educate the public and reduce the harmful impact of opioids. Operation Naloxone is an initiative of the Student College of Clinical Pharmacy at the University of Houston College of Pharmacy with the goal of educating the public through standardized presentations. The study's purpose is to utilize the presentation to assess changes in knowledge and attitudes of laypersons regarding opioid overdoses and naloxone administration using a validated survey. Objective: To determine the change in scores from baseline in response to a standardized and reproducible presentation given by the Operation Naloxone initiative. Methods: The participants of the study include high school students. Immediately before the presentation, participants complete a presurvey. All surveys are numbered, allowing answers to remain anonymous. The participants attend a 1‐hour presentation provided by Operation Naloxone, then immediately complete a postsurvey. The primary end points for data analysis are the changes in Opioid Overdose Knowledge and Attitudes Scale scores. Results: Data were recorded for this study starting in October 2019 and ended in May 2020; 174 paired surveys, 87 pre‐ and 87 postsurveys, were included in data analysis of the four knowledge domains. When combined, the four knowledge domains resulted in statistically significant ( P < .0001) increases between presurvey scores (mean, 19.54) and postsurvey scores (mean, 23.39). The combined attitude scale including all 10 questions resulted in a statistically significant ( P < .0001) increase in attitude scores from presurveys (mean, 41.29; median, 42) to postsurveys (mean, 43.97; median, 45). Conclusion: The current study found statistically significant increases in both knowledge and attitudes domains of high school students regarding opioid overdoses. The study should be reproduced in different age groups and demographics to determine whether there is a large scope of impact on the community.